Peran Badan Pengawas Obat dan Makanan (BPOM) dalam Pengendalian Resistensi Antimikroba di Indonesia - Muthia Izati; Patihul Husni; Yosita Aulia Mustofa (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Antimicrobial resistance when microbes such as bacteria, viruses, fungi, and parasites bo longer respond to antimicrobial medicines. Antimicrobial resistance is one of the 10 health threats faced by the global community. Controlling antimicrobial resistance involves various governmental agencies, including the Indonesia Food and Drug Authority (BPOM), which has responsibilities in the field of drug and food surveillance in Indonesia. The article is prepared to examine the role of BPOM in the Control of Antimicrobial Resistance in Indonesia. The article is prepared using a normative approach, which is a study of articles referring to normative laws found in legislation. The role of BPOM role in antimicrobial resistance control in Indonesia includes the drafting, strengthening, and implementation of policies surveillance of antimicrobial lifecycle, public education, and conducting joint inspection inspection with relevated institutions. The results of this article show that controlling antimicrobial resistance in Indonesia requires coordination and cooperation from all relevant institutions.